Asuhan Keperawatan Keluarga Tn. K Dengan Gangguan Sistem Endokrin : Diabetes Melitus di Desa Kalibuntu Rt 04 Rw 02 Kecamatan Losari Kabupaten Brebes - Mohammad Rizki Wahyudi; Esti Nur Janah; Siti Fatimah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The development of time has changed the types of diseases from infectious to non-communicable or degenerative such as asthma, cancer, stroke, chronic kidney disease, diabetes, and hypertension that are influenced by lifestyle, nutrition, and physical activity. Insulin resistance or lack of pancreas triggers diabetes mellitus, causing hyperglycemia that damages the nervous system and blood vessels. International Diabetes Federation predictions show an increase in diabetes mellitus cases worldwide, including in Central Java, which ranks second only to hypertension. Diabetes mellitus can be identified through blood glucose monitoring and symptoms include hunger, thirst, and frequent urination. Risk factors for diabetes include age, genetics, obesity, inactivity, hypertension, dyslipidemia, and poor nutrition. Prevention and management of diabetes can be done through family care that involves educators, counselors, and collaborators to help families manage the disease well. This study examines the nursing care of Mr. K's family. K with endocrine system disorders Diabetes Militus in Kalibuntu Village, Losari District, Brebes Regency, with the results of the patient's lack of understanding about diabetes and rarely doing exercise.